SAT0399 EFFECT OF DISEASE-MODIFYING ANTI-RHEUMATIC DRUGS ON BONE STRUCTURE AND STRENGTH IN PSORIATIC ARTHRITIS PATIENTS. (June 2019) - Simon, David; Bayat, Sara; Tascilar, Koray; Kampylafka, Eleni; Meinderink, Timo; Schuster, Louis; Liphardt, Anna-Maria; Rech, Jürgen; Hueber, Axel; Schett, Georg; Kleyer, Arnd
Abstract : Background: In contrast to rheumatoid arthritis, little is known about the effect of disease modifying anti-rheumatic drugs (DMARDs) on bone structure and bone biomechanics in psoriatic arthritis (PsA). Objectives: To address whether the use of methotrexate (MTX) and biological DMARDs (bDMARDs) impacts bone structure and biomechanical properties in PsA patients. Methods: Cross-sectional study in PsA patients receiving no DMARDs, MTX or bDMARDs. Volumetric bone densities (vBMD), microstructural parameters and biomechanical properties (stiffness/failure load) were determined by high-resolution peripheral quantitative computed tomography (HR-pQCT) and micro-finite element analysis. Bone parameters were compared between PsA patients with no DMARDs and those receiving any DMARDs, MTX or bDMARDs, respectively. Results: 165 PsA patients were analyzed, 79 received no DMARDs, 86 received DMARDs, of them 52 bDMARDs (TNF, IL-17- or IL-12/23 inhibitors) and 34 MTX. Groups were balanced for age, sex, comorbidities, functional index and bone-active therapy, while disease duration was longest in the bDMARDs group (7.8±7.4 years), followed by the MTX group (4.6±7.4) and the no-DMARD group (2.9±5.2). No difference in bone parameters was found between the no-DMARD group and the MTX group. In contrast, the bDMARDs group revealed significantly higher total (p=0.001) and trabecular vBMD (p=0.005) as well as failure load (p=0.012) and stiffness (p=0.012). In regression models age and bDMARDs influenced total vBMD, while age, sex and bDMARDs influenced failure load and stiffness. Conclusion: Despite longer disease duration bDMARDs treated PsA patients benefit from higher bone mass and better bone strength than PsA patients receiving MTX or no DMARDs. These data support the concept of better control of PsA-related bone disease by bDMARDs. Disclosure of Interests: David Simon Grant/research support from: Novartis, Consultant for: Lilly, Speakers bureau: Janssen, Sara Bayat: None declared, Koray Tascilar: None declared, Eleni Kampylafka: None declared, Timo Meinderink: None declared, Louis Schuster: None declared, Anna-Maria Liphardt Grant/research support from: Novartis Pharma GmbH, Jürgen Rech Grant/research support from: Bristol-Myers Squibb and Celgene (greater than $10, 000), Consultant for: Bristol-Myers Squibb, Celgene, Chugai, GlaxoSmithKline, Janssen, Eli Lilly, Novartis, Roche, Sanofi Aventis, and UCB (in total more than $10, 000), Speakers bureau: Bristol-Myers Squibb, Celgene, Chugai, GlaxoSmithKline, Janssen, Eli Lilly, Novartis, Roche, Sanofi Aventis, and UCB (in total more than $10, 000), Axel Hueber Grant/research support from: Novartis, Pfizer, Lilly, Consultant for: Lilly, GSK, Novartis, Janssen, Celgene, Abbvie, Roche, Speakers bureau: Lilly, Janssen, Novartis, Celgene, Biogen, Abbvie, BMS, Georg Schett: None declared, Arnd Kleyer Grant/research support from: Lilly, Consultant for: Lilly, Speakers bureau: Abbvie